2017
DOI: 10.1371/journal.pone.0174759
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mutational analysis of a nicotinamide mononucleotide deamidase from Agrobacterium tumefaciens showing high thermal stability and catalytic efficiency

Abstract: NAD+ has emerged as a crucial element in both bioenergetic and signaling pathways since it acts as a key regulator of cellular and organismal homeostasis. Among the enzymes involved in its recycling, nicotinamide mononucleotide (NMN) deamidase is one of the key players in the bacterial pyridine nucleotide cycle, where it catalyzes the conversion of NMN into nicotinic acid mononucleotide (NaMN), which is later converted to NAD+ in the Preiss-Handler pathway. The biochemical characteristics of bacterial NMN deam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The MISTIC server 27 (mutual information server to infer coevolution) was used to analyse and visualize the extent of the coevolutionary relationship between two positions in the bacterial PARP protein family by using the information contained within the above MSA (multiple sequence alignment) 28 . The mutual information (MI) obtained is usually used to find structurally or functionally important positions in a given protein fold family 29 , 30 . The residue-based Kullback-Leibler conservation score (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MISTIC server 27 (mutual information server to infer coevolution) was used to analyse and visualize the extent of the coevolutionary relationship between two positions in the bacterial PARP protein family by using the information contained within the above MSA (multiple sequence alignment) 28 . The mutual information (MI) obtained is usually used to find structurally or functionally important positions in a given protein fold family 29 , 30 . The residue-based Kullback-Leibler conservation score (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal stability of the above PARPs was also studied under different conditions by monitoring Sypro Orange fluorescence while heating the samples, and determining the midpoints of the transitions (melting temperature or T m) 30 . Previous investigations showed that this assay provides a good estimate of binding affinity, optimal storage pH and the suitable protein stabilizers to be used 40 , 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusobacterium mortiferum ATCC 9817 TARG1 macrodomain (Uniprot code, C3WDV1) was cloned into the pSol-AFV vector (Lucigen, USA), using the synthetic FMAG_01619 gene obtained from Genscript (USA), and transformed into Escherichia coli 10G 57 . The clone containing the FmTARG1 was grown in 1 L of Terrific Broth (TB) medium supplemented with kanamycin (50 µg mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although yPDE2 has previously been purified and characterized [7,9], this is the first time that the heterologous expression of this enzyme has been considered. E. coli was selected because it is easy to manage for protein expression [30]. The available UniProt sequence was used to construct an IPTG-induced vector and Rosetta 2 E. coli strain was transformed.…”
Section: Ypde2 Expression and Assaymentioning
confidence: 99%